Histomorphological Changes of Apelin Treatment in Renal Tissue in Doxorubicin-induced Nephrotic Syndrome Model - KOÇ, MEHMET; ÖZKAN YENAL, NAZİYE; ÇETİNEL, ŞULE (AVES PRESS LTD, 2016)
Objective: Nephrotic syndrome (NS) may result in renal failure. Apelin (AP), a vasoactive peptide, demonstrates its effect by binding to the AP receptor. AP, present in the endothelial and vascular smooth muscle cells of glomerular arterioles, affects the pre- and post-microvascularization by regulating renal hemodynamics. This study aimed to determine the histomorphological changes of AP treatment in a doxorubicin (DOX)-induced NS model. Methods: Male Sprague Dawley rats were used. Rats were randomly divided into four groups (n=6): control [physiological saline (PS) solution intraperitoneal (i.p.)]; AP+PS (PS and 50 mcg/kg/day AP-13 i.p.); NS [10 mg/kg DOX i.p.] and NS+AP (NSAP; 10 mg/kg DOX+50 mcg/kg/day AP-13 i.p.). Renal tissues were collected on the 22nd day for light microscopic investigations. Results: Light microscopic investigations showed that the NS group revealed adhesions between the tuft and Bowman's capsule, mesangial matrix accumulation in the glomeruli, and tubular damage with dilatation and cast accumulation. In the NSAP group, minimal regression in the glomerular and tubular damage was observed. Conclusion: The histomorphological changes of AP treatment in a DOX-induced NS model demonstrated a limited therapeutic effect on glomerular and tubular damage in renal tissues.
Keywords: Glomerulus; tubules; doxorubicin; nephrotic syndrome; apelin